Experimental investigation on heat transfer on laminar flow over combination of blocks mounted on rectangular channel. (2021) - Dinesh Kumar, V.; Sivasubramanian, M.; Ramkumar, P.; Jaganathan, K.D.
Abstract: The investigation of flow over bluff bodies mounted on a surface invites more attention in various areas of engineering like electronic packing, heat exchangers and cooling systems for nuclear plants etc., It is proposed to study experimentally, the effect of block shape on the flow, spacing between the blocks and heat transfer using combination of square and circular blocks mounted on the flow path. This study presents the results for staggered arrangement of the blocks on the flow passage for different spacing among the blocks and various Reynolds number. The Reynolds number (Re) measured in this study ranges from 80 to 160 and the space for the center to center of the blocks (Lx /Ly ratio) is retained between 2.0 < Lx /Ly < 3.0 with a step of 0.5. Interaction of the heat transfer rate with Re, spacing between the blocks and shape of the blocks are discussed in detail. The blockage ratio (BR) for the analysis is 0.75 and water as working fluid. The result shows that the presence of combination of blocks effects the flow possessions in greater extent.